2018
DOI: 10.1016/j.neuroscience.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid Signaling in Embryonic Neuronal Motility and Cell–Cell Contact – Role of mGluR5 and TRPC3 Channels

Abstract: Cell-cell communication plays a central role in the guidance of migrating neuronal precursor cells during the development of the cerebral cortex. Endocannabinoids (eCBs) have previously been shown to be one of the central factors regulating neuronal migration. In this study the effects of eCBs on different parameters, expected to affect embryonic cortical neuronal motility have been analyzed in neurosphere-derived neuroblasts using time-lapse microscopy. Increased endogenous production of the endocannabinoid 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
(101 reference statements)
0
4
0
Order By: Relevance
“…TRPC3 also enhanced melanoma cell migration and tumor formation both in vitro and in vivo [97]. Furthermore, TRPC3, together with mGluR5, has been shown to enhance motility in embryonic neuronal cells as a result of endocannabinoid stimulation [98]. It has also been shown that the invasion of bladder cancer cells is dependent on both TRPC3 and TRPC6.…”
Section: Trpc Channels Migration and Invasionmentioning
confidence: 94%
“…TRPC3 also enhanced melanoma cell migration and tumor formation both in vitro and in vivo [97]. Furthermore, TRPC3, together with mGluR5, has been shown to enhance motility in embryonic neuronal cells as a result of endocannabinoid stimulation [98]. It has also been shown that the invasion of bladder cancer cells is dependent on both TRPC3 and TRPC6.…”
Section: Trpc Channels Migration and Invasionmentioning
confidence: 94%
“…The migration of neurons into the developing neocortex results in the formation of a six‐layered structure that is ordered by time of migration . Interestingly, Turunen et al found that the increased endogenous production of 2‐Ara‐Gl led to bursts in the mobility of neuroblasts regulated by the metabotropic glutamate receptor 5 (mGluR5) or its transducer canonical transient receptor potential channel 3 (TRPC3) in isolated mice neuronal progenitor stem (NPS) cells . Furthermore, Díaz‐Alonso et al evidenced the key role of the ECS in promoting a correct neuronal migration.…”
Section: The Endocannabinoid Systemmentioning
confidence: 99%
“…AEA is a high‐affinity partial agonist of CB1R and is mostly inactive when bound to CB2R, whereas 2‐AG is a full agonist of both CBRs (Zou and Kumar, 2018) whose structure is strictly recognized by CB2R. The change in 2‐AG affects the distance and rotation frequency among NP cells, which determines the number of contacts between neurons and neurons (Turunen et al, 2018). And by activating CB1R and phosphorylating ERK1/2, 2‐AG not only regulates synapse formation, axonal growth, but also controls the fate, migration, and proliferation of NP cells (Keimpema et al, 2013).…”
Section: Metabolic Pathways and Intracellular Regulation Of Ecbsmentioning
confidence: 99%